Assessing life-space mobility: a systematic review of questionnaires and their psychometric properties - Ullrich, Phoebe; Werner, Christian; Abel, Bastian; Hummel, Merit; Bauer, Jürgen M.; Hauer, Klaus (Zeitschrift für Gerontologie und Geriatrie, 2022)
Life-space mobility (LSM), as the extent of mobility within one’s environment, is a key for successful aging and has become a relevant concept in gerontology and geriatric research. Adequate assessment instruments are needed to identify older persons with LSM restrictions, and to initiate, adapt or evaluate intervention strategies.